EFFECT OF GAMMA IRRADIATION ON SEED GERMINATION, STORAGE, AND SEEDLING GROWTH OF Magnolia champaca L. - Muhammad Zanzibar; Dede J. Sudrajat (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2016)
Gamma irradiation of seeds is known as an important factor in stimulating biochemical and physiological processes. This paper investigates the effect of seed irradiation on the seed germination, storability, and seedling growth traits of Magnolia champaca. Seeds were irradiated with 0, 5, 10, 15, 20, 40, 60, 80 and 100 Gy by Cobalt-60. The treated seeds were grouped into three lots, namely germination test, storage test and seedling growth characteristics. Observations were made for seed germination percentage, germination index, mean germination time, germination value and growth traits such as height, collar diameter, number of leaves, root length, and dry weight. Results showed that irradiation at a dose of 30 Gy was close to LD50, and irradiation at doses of 80 Gy and higher caused lethal effect. The maximum increase of germination parameters on irradiated seed was recorded at a dose of 10 Gy, and then it decreased. Growth rate in terms of seedling height, collar diameter, number of leaves, and dry weight have also increased in gamma irradiation doses up to 80 Gy, but the dose of 10 Gy resulted in survival and growth that was more stable and gave the highest values for most of the parameters. Hence, lower dose (10 Gy) of irradiation treatment can be used to increase seed germination, storability and seedling growth of M. champaca.